Minuta Akta Notaris Dalam Bentuk Elektronik - Ahmad Rifaldi; Habib Adjie (Fakultas Hukum Universitas Narotama, 2022)
Minuta Notary deed is a very important state document, so in its storage notary is obliged to maintain and maintain it properly, stipulated in UUJN Article 1 number 13. The storage of documents minuta notary deed using electronic media has not been regulated in UUJN, but in Article 6 of the ITE Law considers the validity of an electronic document, although the proof according to Article 1866 KUHPer and Article 184 kuhap does not explain the existence of electronic evidence, which is a notary deed is an authentic deed in accordance with UUJN Article 1 number 1. The transition of notary protocols from conventional (paper documents) to electronic documents to protection for notary deeds that are prone to damage due to natural disasters, fires and termites. Electronic storage also avoids excess storage space, the protection of electronic documents has been protected by the ITE Law Article 32 Paragraph (1) and (2) although it has not been regulated directly by UUJN as a notary guideline in the manufacture and storage of minuta deeds as a Notary protocol, this makes it possible for Notaries to have special containers to store minuta deeds as electronic documents. Keywords: Notary, Deed, Electronic, Document